Building production processes planning and management in classical greek era; comparison with contemporary practices - Yılmaz, İbrahim (Konya Technical University Faculty of Architecture and Design, 2023)
Through the example of the Classical Greek Era, the study focuses on seeking an answer to the question of whether managerial techniques and strategies were developed in building production processes in ancient times. The study aims to identify and examine the stages planned in the building production processes and the construction management and organization techniques developed during the Classical Greek period (VI.-IV. century BCE), which played an important role in the development of building art and to compare the practices of the Era with today's construction and management practices. The research methodology is based on the interpretation of historical data from the Classical Greek Era, consisting of construction texts written on stone slabs and their epigraphic explanations, and the comparison of the practices of the Era with contemporary practices. The stone slab samples with the construction texts used in the study were taken from the Sara B. Aleshire Center for Greek Epigraphic Studies catalogs at the University of Berkeley. The epigraphically analyzed descriptions of these inscriptions by different authors were obtained by searching the literature sources through the catalog numbers given to the samples. In the classical Greek Era, three main administrative public bodies made decisions on construction, planning, and managing the construction processes. These include the Senate, Ecclesia (people's assembly), and building commissions. By the decision of the people's assembly, building commissions were established to manage and supervise the construction process from a financial, administrative, and technical perspective. This research has contributed to the understanding that today's building production strategies and management theories have their roots in ancient times, thereby contributing to the universality of construction and management theory. Due to the dynamic nature of the research, the period analyzed was also compared with the current production management theories. The study's uniqueness lies in interpreting historical documents and observing and comparing current conditions. Hence, while the construction and management systems in the Classical Greek period are understood, two different processes are analyzed in their own contexts, and their differences and similarities are highlighted.
Keywords: Construction Management; Construction Production Process; Ecclesia; Greek Period